Creative evolutionary systems - Bentley, Peter, 1972-; Corne, David (San Francisco, CA. : Morgan Kaufmann ; San Diego, CA : Academic Press, 2002)
The use of evolution for creative problem solving is one of the most exciting and potentially significant areas in computer science today. Evolutionary computation is a way of solving problems, or generating designs, using mechanisms derived from natural evolution. This book concentrates on applying important ideas in evolutionary computation to creative areas, such as art, music, architecture, and design. It shows how human interaction, new representations, and approaches such as open-ended evolution can extend the capabilities of evolutionary computation from optimization of existing solutions to innovation and the generation of entirely new and original solutions. This book takes a fresh look at creativity, exploring what it is and how the actions of evolution can resemble it. Examples of novel evolved solutions are presented in a variety of creative disciplines. The editors have compiled contributions by leading researchers in each discipline. If you are a savvy and curious computing professional, a computer-literate artist, musician or designer, or a specialist in evolutionary computation and its applications, you will find this a fascinating survey of the most interesting work being done in the area today. * Explores the use of evolutionary computation to generate novel creations including contemporary melodies, photo-realistic faces, jazz music in collaboration with a human composer, architectural designs, working electronic circuits, novel aircraft maneuvers, two- and three-dimensional art, and original proteins. * Presents resulting designs in black-and-white and color illustrations. * Includes a twin-format audio/CD-ROM with evolved music and hands-on activities for the reader, including evolved images, animations, and source-code related to the text. * Describes in full the methods used so that readers with sufficient skill and interest can replicate the work and extend it. * Is written for a general computer science audience, providing coherent and unified treatment across multiple disciplines.
An introduction to creative evolutionary systems / Peter J. Bentley and David W. Corne -- pt. 1. Evolutionary creativity. Creativity in evolution: individuals, interactions, and environments / Tim Taylor -- Recognizability of the idea: the evolutionary process of Argenia / Celestino Soddu -- Breeding aesthetic objects: art and artificial evolution / Mitchell Whitelaw -- The beer can theory of creativity / Liane Gabora -- pt. 2. Evolutionary music. GenJam : evolution of a jazz improviser / John A. Biles -- On the origins and evolution of music in virtual worlds / Eduardo Reck Miranda -- Vox populi: evolutionary computation for music evolution / Artemis Moroni ... [et al.] -- The sound gallery--an interactive A-life artwork / Sam Woolf and Adrian Thompson -- pt. 3. Creative evolutionary design. Creative design and the generative evolutionary paradigm / John Frazer -- Genetic programming: biologically inspired computation that exhibits creativity in producing human-competitive results / John R. Koza ... [et al.] -- Toward a symbiotic coevolutionary approach to architecture / Helen Jackson -- Using evolutionary algorithms to aid designers of architectural structures / Peter von Buelow -- pt. 4. Evolutionary art. Eons of genetically evolved algorithmic images / Steven Rooke -- Art, robots, and evolution as a tool for creativity / Luigi Pagliarini and Henrik Hautop Lund -- Stepping stones in the mist / Paul Brown -- Evolutionary generation of faces / Peter J.B. Hancock and Charlie D. Frowd -- The Escher evolover: evolution to the people / A.E. Eiben, R. Nabuurs, and I. Booij -- pt. 5. Evolutionary innovation. The genetic algorithm as a discovery engine: strange circuits and new principles / Julian F. Miller ... [et al.] -- Discovering novel fighter combat maneuvers: simulating test pilot creativity / Julian F. Miller ... [et al.] -- Innovative antenna design using genetic algorithms / Derek S. Linden -- Evolutionary techniques in physical robotics / Jordan B. Pollock ... [et al.] -- Patenting evolved bactericidal peptides / Shail Patel ... [et al.].
A continuation of Evolutionary design by computers.
Includes bibliographical references and index.
Keywords: Evolutionary programming (Computer science); Computer-aided design; Evolutionary computation; Creative ability in technology; CD-ROMs.; Electronic books